Productivity driven by Tana river discharge is spatially limited in Kenyan coastal waters. (1st October 2021) - Mutia, Damaris; Carpenter, Stephen; Jacobs, Zoe; Jebri, Fatma; Kamau, Joseph; Kelly, Stephen J.; Kimeli, Amon; Langat, Philip Kibet; Makori, Amina; Nencioli, Francesco; Painter, Stuart C.; Popova, Ekaterina; et al.
Abstract: The Tana River is the longest river system in Kenya (~1000 km) and contributes ~ 50% of the total river discharge to Kenyan coastal waters. The river discharges significant amounts of nutrients and sediments, reaching ~24, 000 tons per day during the rainy season (March–April), into Ungwana Bay (North Kenya Banks). The bay is an important habitat for high-value Panaeid prawn species which sustain important small-scale fisheries, semi-industrial bottom trawl prawn fisheries, and is the livelihood mainstay in the surrounding counties. In this study we analysed >20 years of satellite-derived chlorophyll-a observations (Chl-a, an index of phytoplankton biomass), along with in situ river discharge and rainfall data, to investigate if the Tana River discharge is a major driver of local phytoplankton biomass in Ungwana Bay and for the neighbouring Kenyan shelf. We find that during the rainy inter-monsoon (March–April), a significant positive relationship (r = 0.63, p < 0.0001) exists between river discharge and phytoplankton biomass. There is a clear time-lag between rainfall, river discharge (1-month lag) and local chlorophyll biomass (2-months lag after discharge). Unlike offshore waters which exhibit bi-annual chl-a peaks (0.22 mg m −3 in February, and 0.223 mg m −3 in August/September), Ungwana Bay displays a single peak per annum in July (2.51 mg m −3 ), with indications that river discharge sustains phytoplankton biomass for several months. Satellite-derived observations and Lagrangian tracking simulations indicate that higher Chl-a concentrations remain locally within the bay, rather than influencing the broader open waters of the North Kenya Banks that are mainly impacted by the wider oceanic circulation. Graphical abstract: Image 1 Highlights: Statistically significant positive correlation between Tana River discharge and Chlorophyll-a in Ungwana Bay. No such correlation away from coastal areas. Productivity over outer North Kenya Banks likely driven by oceanic processes (upwelling) rather than Tana discharge.